Health Promotion among Mentally Ill People in Nepal - Ghimire, S. R.; Dhungana, M; Bhagat, S; Parajuli, S (Journal of Psychiatrists’ Association of Nepal, 2015)
Mental health is a neglected area and the activities to promote mental health are limited in Nepal. Exploration of various social determinants of mental health is needed prior to starting mental health promotion that do not only lie within health sector but also deeply rooted outside. Mental health promotional and preventive program needs to be locally relevant, culturally appropriate and cost effective, and require social and public health approaches. Provision of community mental health strategy to the door step of people can be an effective strategy to promote health among mentally ill population. Health sector needs to be coordinated and collaborated with other sectors to address the complex mental health problems. Consideration of cultural and religious aspect in health care systems is essential to ensure that every community are equally respected and are treated equally despite variation. J Psychiatric Association of Nepal Vol .3, No.2, 2014, pp-3-8 DOI: http://dx.doi.org/10.3126/jpan.v3i2.12378